The effect of mix impact aerobic exercise on reducing abdominal circumference and body weight - Risa Dw Nuraini; Said Junaidi (Universitas Sriwijaya, 2023)
Abdominal circumference and body weight are parameters that provide an overview of body mass. To maintain ideal body mass, you can do mix impact exercise. The purpose of this study was to determine the effect of mix impact gymnastic exercises on reducing abdominal circumference and body weight in members of the Sogati studio. This research is experimental research with a pretest-posttest design. The research instruments used were abdominal circumference and weight assessment forms, stopwatch, sound, digital scales, measuring tape. The population of this study were all 90 members of the Sogati studio. The sample in this study consisted of 20 members using a purposive sampling technique. The results of this study show the results of the T test in the group with decreased abdominal circumference tcount= 4.122 > ttable= 1.725. And the results of the T test in the weight loss group tcount= 3.572 > ttable= 1.725. So, it can be concluded that there is an effect of mix impact training on reducing abdominal circumference and body weight in Sogati studio members.